Structural behavior prediction of the Butterfly-shaped and straight shear fuses. (October 2021) - Farzampour, Alireza
Abstract: Structural fuses can be implemented in buildings as steel plates subjected to shear loading. Strategically engineered cut-outs in these steel plates can be used to create shear fuses with energy dissipating capability. The structural fuses are used to protect the surrounding structure from damages and significant inelastic deformations, and then be replaceable after a major earthquakes. Previous studies indicate that structural fuses with shear fuses improve the initial elastic stiffness, energy dissipation capability, and ductility of structures. Butterfly-shaped fuses with varying width between larger ends and a smaller middle section have been used to better align bending capacity with the moment demand along the length of the fuse. These fuses have been shown in previous tests to be capable of substantial ductility and energy dissipation. In this study, equations are developed to capture load–displacement behavior of butterfly-shaped and straight shear fuses. The butterfly angle, defined as the angle between intersections of the inclined edges at the middle of the fuse, is investigated. Using the flexural and shear limit state equations, the critical butterfly angle identifying the transition from the shear to flexure is proposed. Subsequently, equations describing the geometric hardening of butterfly-shaped shear fuses are proposed. Along the same lines, the stiffness of a typical butterfly-shaped fuse is developed by dividing the stiffness into four major parts: fuse flexural deformations, fuse shear deformations, and shear and flexure deformations of the end zones. In addition, the post-yielding hardening behavior is investigated considering axial forces generated under shear loading deformations. Subsequently, computational finite element models are presented and validated with laboratory tests for two different configuration examples to examine the implementation of the proposed limit state prediction. To verify the provided applicability of the proposed analytical equations, a set of computational models are considered, and the associated backbone behavior of the models are compared with their corresponding proposed equations. The procedures presented in this paper to predict the behavior of fuses could be useful for the design of butterfly-shaped fuses with more than 90% accuracy in predicting the backbone behavior of the fuse system.